The Transformative Role of Nanotechnology: Enhancing Solar Energy Conversion, Revolutionizing 3d Printing, And Engineering Superhydrophobic Surfaces - Ahuja, Mehul (Emerging Frontiers Library for The American Journal of Applied Sciences, 2026)
This paper explores the multifaceted applications of nanotechnology across three diverse yet impactful fields: solar energy, 3D printing, and superhydrophobic nanocoatings. It delves into how nanoscale manipulation of materials significantly enhances the efficiency and cost-effectiveness of solar photovoltaic devices, revolutionizes additive manufacturing by enabling precision and novel material properties, and creates self-cleaning, water-repellent surfaces with broad industrial applications. By examining recent advancements and prospects in each area, this paper highlights the profound and transformative potential of nanotechnology to address critical challenges in energy, manufacturing, and materials science.